(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This study was conducted on two palm trees planted using cores, within the College of Arts and Sciences - Tokra, and at the same age stage, where the lesson on manual pollination of palm plants was applied practically to the students of the course “Students of the Department of Botany and students of the Department of Zoology” on the palm tree during its first flowering, during Spring semester 2021 on March 30, documenting the pollination process in a visual recording, following all stages and taking pictures of them, starting from pollination until fruit ripening, to keep them and benefit from them as a practical reference using educational technology for students of the department, college and university, as practical application helps. To consolidate the information and increase the student’s skill, while leaving the other palm tree for natural pollination (by wind). The results of manual pollination were satisfactory, despite not fertilizing the soil or adding any mixtures to it, and relying on rain water only for irrigation, but the pollination process was successful and the fruits were set and the fruits ripened and became dates, then moist and almost close in size, and inside it is a seed (kernel) And its fruits were of better quality than the fruits of air pollination, which were ripened without pollination and did not contain a seed inside, on which we noticed a difference in the size of the fruits, crowding of the fruits in the jugular, dryness and shrinkage of some of them, turning them into a reddish-brown color, and then falling off.